Effects of food waste sandwiched compost on Bok Choy seeds, plants and soil properties - Phooi, Chooi Lin (2023)
Food waste contributes to greenhouse gas emissions and pollution when disposed of in landfills. Finding sustainable ways to reduce it is crucial. Sandwich compost, a modified form of Bokashi, is a promising solution that converts food waste into a nutrient source for plants. The impact of sandwich compost on soil-plant growth is not well-known. To address this, a study had three objectives: (i) to evaluate the effect of sandwiched compost leachate as a priming solution on Bok Choy seed germination performance; (ii) to evaluate the effect of sandwiched compost substrate amendment on soil physical-chemical properties and enzyme activities; and (iii) to evaluate the effect of sandwiched compost amendment on nutrient composition and antioxidants in Bok Choy compared to commercially grown plants. A self-made sandwich compost bucket was used in the study. Raw and cooked food waste, including plant and animal-based materials in a 3:2 ratio (raw:cooked), were collected locally. Alternate layers of sandwich compost bran and food waste were filled in the bucket, compacted, and covered tightly. The mixture was fermented for two weeks, and the resulting leachate and substrate were used in the research. Bok Choy seeds were treated with three methods in the first study: T1-Bio-nutripriming (0.2% of sandwiched compost leachate), T2-Hydropriming, and T3- Control (dry seeds) for 34 days. The experiment was designed using Completely Randomized Design (CRD) with three replications. The results showed that priming with sandwiched compost leachate improved germination time by 33.2% and increased SPAD unit by 28.6%. However, there was no significant difference in root and shoot dry matter among the treatments. Study 2 used a Completely Randomized Design to investigate soil-to-substrate ratios and incubation periods on soil properties and enzyme activities. Results showed that a 1:1 ratio for four weeks significantly improved soil quality, with substrate amendment playing a key role in improving soil-plant quality. This led to significant increases in soil urease activity, pH, and CEC compared to preamendment, and increased microbial activity positively affected nutrient availability, improving plant growth. The study suggests that sandwich compost can enhance soil quality as a soil amendment. Study 3 investigated the use of sandwiched compost substrate as a soil amendment, seed priming solution, and liquid fertilizer for Bok Choy growth. Results showed high yield potential and a high SPAD unit (26.50-37.77). The third cycle produced the highest total leaf area (71.78-141.73 cm2), and the fourth cycle produced Bok Choy with high total carotenoid content (521.60 mg g- 1). However, root growth was not favorable, suggesting that Sandwiched compost may not be suitable for root crops in the first two growing cycles due to the possible presence of arbuscular mycorrhizal fungi. Sandwiched compost substrate improves soil-plant quality, Bok Choy growth and nutrient content. Optimal soil-to-substrate incubation is 1:1 for four weeks. Sandwiched compost can be used as a soil amendment, seed priming solution, and liquid fertilizer. Further research is needed to determine its effectiveness for root crops.